2004
DOI: 10.1021/cg0341959
|View full text |Cite
|
Sign up to set email alerts
|

Variable Temperature Studies of a Polymorphic System Comprising Two Pairs of Enantiotropically Related Forms:  [S,S]-Ethambutol Dihydrochloride

Abstract: Of the four known polymorphs of [S,S]-ethambutol dihydrochloride, two transform in an enantiotropic single-crystal-to-single-crystal phase transformation from Form II to Form I on heating. The crystal structures of these two forms have been solved and compared. Because the other two forms are metastable and are only obtained from the melt, single-crystal data could not be obtained on them. However, all four forms have been characterized, and their relative thermodynamic relationships have been investigated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 15 publications
4
18
0
Order By: Relevance
“…normal ranges (Allen et al, 1987) and are similar to those observed in the corresponding chloride (Hamalainen et al, 1985;Rubin-Preminger et al, 2004) and bromide (Godfrey et al, 1992) salts. The crystal structure is stabilized by extensive intermolecular O-HÁ Á ÁN and N-HÁ Á ÁO hydrogen bonding, linking cations, anions and water molecules into a threedimensional network ( Fig.…”
supporting
confidence: 84%
“…normal ranges (Allen et al, 1987) and are similar to those observed in the corresponding chloride (Hamalainen et al, 1985;Rubin-Preminger et al, 2004) and bromide (Godfrey et al, 1992) salts. The crystal structure is stabilized by extensive intermolecular O-HÁ Á ÁN and N-HÁ Á ÁO hydrogen bonding, linking cations, anions and water molecules into a threedimensional network ( Fig.…”
supporting
confidence: 84%
“…This can be attributed to rotational/inversion processes that contribute to the site-exchange effect forming a single peak at 180°C. 16,19,20 This process would require the breaking and formation of hydrogen bonds due to the dehydration process. Furthermore, peaks observed at 62 and 139 ppm at a low temperature were observed as two peaks at 63 and 60 ppm and 141 and 137 ppm, respectively, at 180°C.…”
Section: Resultsmentioning
confidence: 99%
“…Form II exhibits a smaller cell volume than form III (at the transition point), which means that form II is more densely packed. This transition to a denser high temperature phase is surprising as the density rule40 would suggest that the high temperature form in an enantiotropic system (form with the higher zero point energy) exhibits a lower density than the (at 0 K) thermodynamically stable form, which has been verified in other pairs of enantiotropically related polymorphs such as cinacalcet HCl,41 D,L-norleucine,9,10 or ethambutol hydrochloride 42…”
mentioning
confidence: 89%